USIA LAYANAN IPAL SEMANGGI KOTA SURAKARTA BERDASAR PENGGUNAAN AIR DAN VOLUME LIMBAH CAIR RUMAH TANGGA - Siti Qomariyah; Adi Yusuf Muttaqin; Budi Utomo (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2018)
Sanitation is a problem of big cities related to its domestic waste water. In the city of Surakarta, the wastewater treatment plant of Semanggi is a centralized wastewater treatment system covering the south area of the city that consists of 28 villages with 9323 customers of home connections. This study examined the useful life of the services of the Semanggi plants based on the volume of water use and waste water. The study applied a descriptive method and resulted in only 17% - 26% of domestic wastewater in the service areas that could be treated by the plant having capacity of 60 liter/second in the year of 2017. Based on the projection of customers, for water use by 170, 160, and 150 liter/person/day, the waste water treatment plant of Semanggi will only treat the waste water by the year of 2020, 2022, and 2024 respectively.